2014
DOI: 10.1088/0967-3334/35/5/763
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative description of the 3D regional mechanics of the left atrium using cardiac magnetic resonance imaging

Abstract: The left atrium (LA) plays an important role in the maintenance of hemodynamic and electrical stability of the heart. One of the conditions altering the atrial mechanical function is atrial fibrillation (AF), leading to an increased thromboembolic risk due to impaired mechanical function. Preserving the regions of the LA that contribute the greatest to atrial mechanical function during curative strategies for AF is important. The purpose of this study is to introduce a novel method of regional assessment of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…11,12 The striking differences in contributions to active and passive atrial emptying from different regions led Kuklik et al to suggest that ablation in regions with greater mechanical function should be minimized to preserve global atrial function. 13 Given the availability of multiple widely accepted ablation procedures that target different regions of the atrium, it may be possible to choose procedures that achieve the goals of restoring normal electrical Pacing Clin Electrophysiol. 2017;40:648-654. c 2017 Wiley Periodicals, Inc. 648 wileyonlinelibrary.com/journal/pace function while preserving mechanical function.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The striking differences in contributions to active and passive atrial emptying from different regions led Kuklik et al to suggest that ablation in regions with greater mechanical function should be minimized to preserve global atrial function. 13 Given the availability of multiple widely accepted ablation procedures that target different regions of the atrium, it may be possible to choose procedures that achieve the goals of restoring normal electrical Pacing Clin Electrophysiol. 2017;40:648-654. c 2017 Wiley Periodicals, Inc. 648 wileyonlinelibrary.com/journal/pace function while preserving mechanical function.…”
Section: Introductionmentioning
confidence: 99%
“…Kuklik reported very similar findings in a separate MRI study: decreased mechanical function in patients with paroxysmal AF compared to controls, and significantly higher mechanical function of the anterior, septal and lateral regions as opposed to roof and posterior regions in both groups. (Kuklik et al, 2014) Speckle-tracking ultrasound gives similar values for strain in these regions, confirming regional variability in atrial function. (Vianna-Pinton et al, 2009)…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 66%
“…Following this reasoning, Kuklik et al suggested that ablation in lateral, anterior and septal regions should be minimized since these regions move the most in both normal and paroxysmal AF atria. (Kuklik et al, 2014) Recently, Moyer et al used a finite-element model of the left atrium to quantitatively evaluate the potential influence of the extent vs. location of ablation scar on atrial function (Figure 4). Starting with a model of the human left atrium validated against both invasive pressure-volume and non-invasive regional wall motion data, (Moyer et al, 2015) Moyer simulated distributions of scar in locations typical of standard pulmonary vein isolation (PVI) and wide area circumferential ablation (WACA) procedures.…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…Notably, regional differences exist in the left atrial segmental function during atrial contraction, with the posterior wall having the lowest motion, probably because its motion is limited by the attachment of the pulmonary veins or compression by the vertebra . In the literature, the areas of the highest motion are controversial; however, this study corroborates a previous study with cardiac magnetic resonance imaging, which observed high mechanical function in the anterior and septal walls. Hence, the myocardial damage, which was indicated by the LVA, of the anterior, septal, and roof walls might have hindered the recovery of the left atrial function following ablation.…”
Section: Discussionmentioning
confidence: 99%